Evaluating the stability of architectural heritage from the perspective of InSAR: a practical study on Jianchuan Ancient Town - Menghua Li; Xinning Gao; Mengshi Yang; Li Tang; Bo-Hui Tang (Heritage Science)
Abstract The increase in human activities and natural degradation often leads to tilting, collapsing, and other forms of deterioration in architectural heritage, posing significant threats to its safety. Therefore, timely detection of abnormal deformation signals in buildings is essential for the protection of architectural heritage. Spaceborne synthetic aperture radar interferometry (InSAR) can detect slight displacements over large areas. However, relying solely on annual mean velocity maps derived from InSAR may not accurately assess the stability of ancient buildings. In this study, we developed a framework that evaluates the stability of individual buildings by integrating the InSAR displacements with building footprints. Vertical and rotational deformations, along with the temporal evolution of these deformations, are combined to generate the results for building stability assessment. We used 74 TerraSAR-X images captured from August 2017 to November 2019 to evaluate the stability of Jianchuan Ancient Town, a renowned National Historical and Cultural City in China. The displacement result suggests that the majority of Jianchuan Ancient Town remains stable, with over 93% of coherent points (CTs) displaying displacement velocities ranging from −5 to 5 mm/yr. Out of the 1,891 buildings in Jianchuan Ancient Town, 1404 are considered stable, 352 are of moderate stability, and 12 are deemed unstable. This study showed the potential of InSAR applications in assessing the stability of architectural heritages, emphasizing its crucial role in heritage preservation and management.